Peran Fungsi dan Tugas Masyarakat dalam Pendidikan: Kajian QS. Al-Ma’un - Yulianti, Ayu; Rikaeni, Ike; Amrullah, Fikri; Djazimi, M.A; Hidayat, Wahyu (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2024)
The role, duties and functions of society in education are very important. There is still a lack of sensitivity in the roles, duties and functions of society in education. Not many local people in the research location have studied up to university. There is still a lack of religious values in the surrounding environment. In QS Al-Ma'un, it states the characteristics of people who deny religion. There are still people who don't care about each other. In QS Al-Ma'un, it is also stated